BRIDGING THE GAP: A STUDY ON THE RELATIONSHIP BETWEEN MINDSET AND FOREIGN LANGUAGE ANXIETY - İrem Altunel (Informascope, 2019)
This study aimed to investigate the relationship between mindset and foreign language anxiety (FLA) of EFL learners at both a private and a state university in Turkey. Quantitative methods were used and two Likert-scales, Foreign Language Classroom Anxiety Scale (FLCAS) and Dweck's Mindset Instrument (DMI) were administered to collect a set of data. Turkish versions of both scales were used during this phase. As well as foreign language anxiety, its three sub-dimensions, which are communication apprehension, test anxiety, and fear of negative evaluation, were also taken account. The study was conducted at the preparatory school of Gazi University and Atılım University, with a total of 203 participants. The findings revealed that there was no statistically significant correlation between mindset and foreign language anxiety. Moreover, EFL learners' foreign language anxiety was found at a moderate level, and it was also explored that they mostly adopted a growth mindset rather than a fixed mindset. Keywords: mindset, foreign language classroom anxiety, EFL learners